Prevalence of Dengue in Students of Arid Agriculture University Rawalpindi - Ikhlak, Ulfat; Irfan, Muhammad; Ali, Shahzad; Ashraf, Asfa; Xiao, Shiwei; Qayyum, Mazhar (PSM Microbiology, 2016)
The incidence of Dengue fever has increased in tropical and subtropical areas including Pakistan. In Pakistan dengue is most prevalent. Dengue fever has emerged as a worldwide problem over the last five years. It has troubled many people across Pakistan including Lahore especially after the floods in 2010. The clinical signs of dengue start from a mild illness to life threatening shock syndrome. There is an urgent need of development of proper treatment for dengue and to create awareness among people. The current study was aimed to find the prevalence of dengue fever in university students. The prevalence of dengue in the university was calculated 17% as we approached 81 people among them 14 were infected with dengue hemorrhagic fever. The disease was more prevalent among females than male population. The disease was more prevalent among younger people. There were 42(65%) people suffering from headache, 19(29%) joint paint, 26(40%) muscle pain and 16(25%) were suffering from abdominal pain out of 64 people among age group 18-23 years. The obtained data was helpful in defining the therapeutic approaches against this emerging infection. Furthermore the relationship of demographic factors like age, gender and socio-economic status with transmission of dengue virus was also being under consideration.